Pengolahan Limbah Cair Sisa Analisis Laboratorium dengan Resin dan Adsorben Karbon Aktif - tri wahono; agus budianto (Institut Teknologi Adhi Tama Surabaya, 2022)
As a company laboratory in East Java produces waste at levels that do not meet the standards permitted by government authorities. The main problem is the COD value, NH3-N levels and pH that are not suitable. The study was conducted to reduce COD levels of NH3-N and neutralize pH with the chosen method. This study aims to determine the effect of the amount of adsorbent and the use of anion exchanger on the pH of the wastewater, the COD concentration of the wastewater, and the total ammonia concentration of the wastewater. This research begins with drying of activated carbon and activation of Silitte MA-12 anion resin. Silitte MA-12 anion resin 100 gr by soaking into the waste and adding activated carbon of 45.5%, 50.55%, 65.72%, 80.89%, and 96.05%. The analysis was carried out after 24 hours of immersion. The Silitte MA-12 resin used causes an increase in pH from 1-2 to 6-7. The results of this study are that the greater the addition of activated carbon percent does not significantly affect the final pH of the sample, the COD value produced is getting smaller from the initial value of 1592 mg/L to 40-200 mg/L with a standard value of 200 mg/L and ammonia levels. in the sample is getting smaller from the initial value of 752 mg/L to 8-90 mg/L with a standard value of 100 mg/L.